OC-027 The use of lanreotide for the management of small bowel angioectasia. (17th June 2017) - Zammit, SChetcuti; Sanders, D; Sidhu, R
Abstract : Introduction: Small bowel angiectasias (SBA) have been reported on capsule endoscopies in up to 60% of patients who present with obscure gastrointestinal (GI) bleeding. They are commonly found in elderly patients with multiple co-morbidities who might be deemed high risk for double balloon enteroscopy (DBE) and argon plasma coagulation (APC). A proportion of patients continue to have recurrent bleeding despite endoscopic therapy. Pharmacological therapy can thus be a useful adjuvant treatment. The aim of this study was to assess the role of Lanreotide (long-acting somatostatin analogue) in patients with refractory GI bleeding. Method: Patients with confirmed SBAs who were started on Lanreotide between January 2010 and December 2016 were included in this study. Baseline demographics were recorded. Efficacy was evaluated in terms of improvement in mean haemoglobin, transfusion requirements and bleeding episodes (>2 g/dl drop in HB or overt bleeding). Results: Twelve patients (67% males, mean age 74 SD ±15.5 years), started on lanreotide were included. All patients had multiple comorbidities including ischaemic heart disease (92%), respiratory problems (59%), diabetes (58%) and chronic kidney disease (50%). Three patients (25%) had hereditary haemorrhagic telangiectasia. Fifty percent was on warfarin whilst 8% were on clopidogrel. Seventy-five percent of patients were on oral iron supplements, 17% were on intravenous iron and 33% were on tranexamic acid. The angioectasias were distributed in the small bowel in 66.7%, small bowel and colon in 8.3% and small bowel and stomach in 25%. Lanreotide was given at a dosage of 60 mg (42%), 90 mg (33%) or 120 mg (25%). It was given at a 4 weekly interval in 75% of patients and at a 6 weekly interval in 17% of patients. One patient (8%) received a single dose. The mean duration of treatment was 19 months SD ±14.5 (range 1–41 months). Only 17% of patients had their lanreotide stopped due to cholelithiasis. There was a significant improvement in mean baseline and follow up haemoglobin levels with lanreotide therapy: 86.8 vs 98.0 (131–166 g/L).(p=0.012) Mean number of bleeding episodes improved with lanreotide use (4.18 vs 1.09 p=0.010). There was a significant improvement in the number of packed red cells (PRCs) received before and after lanreotide (total PRCs: 323 vs 152 p=0.006; PRCs over 12 months: 275 vs 126 p=0.055). Patients required a reduced number of DBEs±APCs after starting lanreotide (n=11) when compared to before (n=19) (p=0.048). Conclusion: Lanreotide is a useful adjuvant treatment with therapeutic enteroscopy in patients with refractory obscure GI bleeding due SBA. It effectively improves haemoglobin, reduces transfusion requirements, bleeding episodes and reduces the number of DBEs needed in difficult to treat patients. Overall, it has a good safety profile. Disclosure of Interest: None Declared